Historizing the concept of family - Lucifora, Cristiane De Assis [UNESP]; Muzzeti, Luci Regina [UNESP]; Reina, Fabio Tadeu [UNESP] (Univ Federal Sergipe, 2021)
Nowadays, we observe that the concept of family continues to change for/in society. The birth of the feeling of childhood is problematized as one of the factors present in the formation of the modern concept of family, since it considers the space that the child starts to occupy in society. Therefore, this work reflects on how the concept of family flourished, manifesting itself as arbitrary. The importance of historical penetration is pointed out as a way to deconstruct this conceptual rooting that, in a natural way, transits through the various fields, excluding family arrangements that differ from the assumed norm, known as patriarchal. It is research with a qualitative approach of bibliographic character with a theoretical framework on the proposed theme. The analysis is based on the praxiology of Bourdieu. The results showed that there is a need to include in the formation of students and teachers questions about the various concepts of family and their implications in school practice. Thus, it is considered that there is a need to think and act on the permeated concepts of family, so that a new paradigm, this time more marked by tolerance, can emerge so that in fact all family formations can enjoy relationships that exist in this milieu.
Keywords: Child and childhood feeling; Families; Family arrangements